Incisional hernia after extreme lateral interbody fusion on the lumbar spine: A case report. (January 2021) - Wakabayashi, Masakazu; Miyazaki, Yurika; Aoki, Kana; Yoshida, Hayato; Minoshima, Kou; Kimura, Tomohiro; Domoto, Yoshinori; Hosaka, Miki; Funatsu, Kentarou; Aisaki, Kazuo; Hokari, Takeo
Highlights: Extreme lateral interbody fusion is a minimally invasive lateral transpsoas approach for spine surgery. The risk of abdominal wall incisional hernias following spinal surgeries needs to be recognized as a possible complication. Laparoscopic repair for abdominal wall incisional hernia after spine surgery is safe and feasible. Abstract: Introduction: Extreme lateral interbody fusion is a minimally invasive lateral transpsoas approach for spine surgery. We herein report a case of an incisional hernia after an extreme lateral interbody fusion on the lumbar spine that was successfully treated by laparoscopic surgery with intraperitoneal onlay mesh repair. Presentation of case: A 78-year-old woman was referred to our hospital with a complaint of left abdominal bulge and pain. She had undergone an extreme lateral interbody fusion for a lumbar spinal canal stenosis from L1 to L4 a year prior. Abdominal computerized tomography showed a left lumbar incisional hernia, and laparoscopic surgery was performed. The hernia orifice was sutured closed and covered with mesh. The patient was discharged five days after the operation with no complications. Discussion: When performing XLIF for a spinal disorder, the muscles should be separated bluntly along their fibers to prevent muscle atrophy, and the incised fascia should be securely sutured closed. Abdominal wall incisional hernias can occur after spinal surgeries such as extreme lateral interbody fusion. Conclusion: Laparoscopic repair for abdominal wall incisional hernia after spine surgery is safe and feasible.